2017
DOI: 10.1186/s41601-016-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

Least square and Kalman based methods for dynamic phasor estimation: a review

Abstract: The characterization of sinusoidal signals with time varying amplitude and phase is useful and applicable for many fields. Therefore several algorithms have been suggested to estimate main aspects of these signals. Within no standard approach to test the properties of these algorithms, it seems to be helpful to discuss a large class of algorithms according to their properties. In this paper, six methods of estimating dynamic phasor have been reviewed and discussed which three of them are based on least square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…It can be concluded that the error occurring is above all the results of the introduced delay, similar to that of [15,21]. Owing to the modification made in calculating the parameters of the phasors, the magnitudes of this calculated error are smaller than in other methods based on the least squares method, with their size becoming comparable to [16,17,23,38], therefore being much smaller than [27,[39][40][41]. The proposed approach can calculate the derivatives of the phasor-phasor speed and acceleration, which reduces the estimation error.…”
Section: Simulation Resultssupporting
confidence: 65%
“…It can be concluded that the error occurring is above all the results of the introduced delay, similar to that of [15,21]. Owing to the modification made in calculating the parameters of the phasors, the magnitudes of this calculated error are smaller than in other methods based on the least squares method, with their size becoming comparable to [16,17,23,38], therefore being much smaller than [27,[39][40][41]. The proposed approach can calculate the derivatives of the phasor-phasor speed and acceleration, which reduces the estimation error.…”
Section: Simulation Resultssupporting
confidence: 65%
“…According to (11), we calculate the phasor matrix H of multi channels by a least square algorithm, as well. According to (10) and (11), the middle matrices have the size of (m × N ) − by − 2 where m is number of channels and N is number of sample per cycle.…”
Section: Generalized Multi-channel Pronymentioning
confidence: 99%
“…There are a number of research initiatives that investigate algorithms for phasor estimation [10], [11]. An adaptive filter is suggested in [12] to estimate phasors.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency and the rate of change of frequency are obtainable in this step. Finally, the amplitude and the phase are obtained by equation (2).…”
Section: First-order Prony Algorithmmentioning
confidence: 99%
“…Fast and precise estimation is also necessary for accurate decision in power system control. In the context of phasor estimation, there are several initiatives that investigate algorithms for phasor estimation [1], [2]. An adaptive filter is suggested in [3] to estimate phasors.…”
Section: Introductionmentioning
confidence: 99%